The RELATIONSHIP BETWEEN ADOLESCENT KNOWLEDGE AND THE ROLE OF PARENTS WITH ADOLESCENT RISKY SEXUAL BEHAVIOR IN BATUROTOK VILLAGE, SUMBAWA REGENCY - Afilda Munawarah; Endyka Erye Frety; Atika (Indonesian Midwifery and Health Sciences Journal, 2023)
Abstract BACKGROUND : These days teenagers relationship and dating styles tend to be risky and negative. The results of a preliminary studies showed that several teenagers conveyed their dating pattern, usually holding hands and hugging at school. It was known that not much reproductive health education  given to students due to the meager condition of schools and villages. Based on data obtained from the local civil registry office, 30% of the 66 brides who registered marriages in 2020 were a teenagers. Meanwhile, there were data obtained from the Public Health Center showed that 18% by total 28 pregnant women who came for a general check up were a middle and late teens. In addition, the health worker in the village explained that in the last two years there have been several cases of teenagers being exposed to sexually transmitted infections, as well as unwanted pregnancies, some of that case was the result of abused by their parents. The purpose of this research was to analyze the relationship between adolescent knowledge and the role of parents with risky sexual behavior in adolescents in baturotok village, Sumbawa Regency. METHOD : the design of this research is using a cross sectional with a simple random sampling. The ammount of the sample used is this research are 100 respondents. I spread the questionnaire directly accross the students of this school. The independent variables of this research are adolescents knowledge and parents. And the dependent variable of this research is risky sexual behaviour. This research is using Spearman rho statistical correlation analysis in SPSS 21.0 for windows. RESULT : The result of this research  indicate that there was a correlation between adolescent knowledge toward a risky sexual behavior(p=0,000, rs=0,681). There was no significant relationship between parents role and risky sexual behavior in Baturotok Village, Sumbawa Regency (p=0,551, rs=-0,060). CONCLUSION : The higher level of adolescent knowledge, would tends the sexual behavior to be low risk and not risky. While the role of parents does not have a significant on the risky sexual behavior of a adolescents in Baturotok village, Sumbawa Regency.